2011
DOI: 10.1103/physrevlett.107.166101
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of the Growth Mode of Graphene on SiC(0001) andSiC(0001¯)

Abstract: We have determined the growth mode of graphene on SiC(0001) and SiC(0001¯) using ultrathin, isotopically labeled Si(13)C "marker layers" grown epitaxially on the Si(12)C surfaces. Few-layer graphene overlayers were formed via thermal decomposition at elevated temperature. For both surface terminations (Si face and C face), we find that the (13)C is located mainly in the outermost graphene layers, indicating that, during decomposition, new graphene layers form underneath existing ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 16 publications
2
30
0
Order By: Relevance
“…Older graphene sheets are lift up by the formation of the new graphene sheet, and the oldest graphene sheet remains on the topmost. This mechanism is consistent with the experimental observations [75,76]. The experiment further revealed that this mechanism is also applicable to the C-face as well as the Si-face [76].…”
Section: Discussion On Quasi-stable Buffer Layer Structuresupporting
confidence: 80%
“…Older graphene sheets are lift up by the formation of the new graphene sheet, and the oldest graphene sheet remains on the topmost. This mechanism is consistent with the experimental observations [75,76]. The experiment further revealed that this mechanism is also applicable to the C-face as well as the Si-face [76].…”
Section: Discussion On Quasi-stable Buffer Layer Structuresupporting
confidence: 80%
“…Because of this strong coupling with the substrate, a buffer layer does not show graphene-like π bands and is electronically inactive [97]. After formation of the buffer layer, further heating leads to decomposition of the SiC bilayers underneath the buffer layer, resulting in nucleation of a new carbon layer (left inset in Figure 15) [98]. It is believed that: (i) the 6 ?…”
Section: Growth Of Graphene On Si Facementioning
confidence: 99%
“…3 layer acts as a template layer for graphene on the Si face, ensuring well-ordered graphene on that surface [99], and (ii) by further Si sublimation, a second 6 ? 3 reconstructed surface forms under the first one which decouples from the substrate and forms monolayer graphene [98].…”
Section: Growth Of Graphene On Si Facementioning
confidence: 99%
“…In the case of epitaxial graphene films on the Si-face of SiC substrates, a carbon-rich buffer layer with partial sp 3 hybridization is always formed [46]. As mentioned above, the buffer layer substantially affects the electronic properties of graphene and causes pinning of the Fermi level and the subsequent reduction of the Schottky barrier height ( Figure 5).…”
Section: Figurementioning
confidence: 99%